Attention and Selection Effects - Sandro Ambuehl; Axel Ockenfels; Colin Stewart (Center for Economic Studies and ifo Institute (CESifo), 2018)
Who participates in transactions when information about the consequences must be learned? We show theoretically that decision makers for whom acquiring and processing information is more costly respond more strongly to changes in incentive payments for participating and decide to participate based on worse information. With higher payments, the pool of participants thus consists of a larger proportion of individuals who have a worse understanding of the consequences of their decision. We conduct a behavioral experiment that confirms these predictions, both for experimental variation in the costs of information acquisition and for various measures of information costs, including school grades and cognitive ability. These findings are relevant for any transaction combining a payment for participation with uncertain yet learnable consequences.
Keywords: D01; 330; rational inattention; incentives; selection effects; cognitive ability; experiment; repugnant transactions